Fibroadenoma/benign phyllodes: a cytologic diagnostic challenge - Yadav, Swati; Sethi, Bhawna; Sangwaiya, Ashok; Singh, Pawan; Satarkar, Rahul N.; Kalhan, Shivani; Thakral, Vibhuti (International Journal of Research in Medical Sciences, 2019)
Background: To study and compare cytomorphological features of histologically proven cases of benign phyllodes and cellular fibroadenoma. Methods: Smears of histologically-proven cases of benign phyllodes and cellular fibroadenoma in one year, were reviewed. The cellular fibroadenoma had epithelial and/or stromal hypercellularity. The stromal and epithelial components as well as the background cells were qualitatively and quantitatively analyzed. Results: Number, cellularity and type of stromal fragments varied significantly in two groups. Higher number, intermediate to large-sized and hypercellular stromal fragments were commonly seen in phyllodes. Hypercellular (3+ cellularity) fragments were seen in 100% cases of phyllodes against 11.1% cases of fibroadenoma. Large-sized stromal fragments were found in 100% of phyllodes while in only 11.1% cases of fibroadenoma. The ratio of number of epithelial to stromal fragments was significantly high (58.5:1) in fibroadenoma against phyllodes (1.3:1). The epithelial architecture, atypia, apocrine metaplasia and presence of cystic macrophages did not very much in the two groups. The cellularity of the dispersed cells in background did not reveal significant difference though the type of cells varied; the proportion of long and short spindle cells was higher in PT group while proportion of oval cells was higher in FA group. Conclusion: The number, cellularity and nature of stromal fragments, ratio of epithelial to stromal fragments, cellularity and type of background cells are helpful in distinguishing benign phyllodes from cellular fibroadenoma. The identification of these features can improve the pickup rate of phyllodes tumor, thereby assisting proper management.